Assessing the link between witnessing inter-parental violence and the perpetration of intimate partner violence in Bangladesh. (December 2017) - Islam, Md.; Rahman, Mosiur; Broidy, Lisa; Haque, Syed; Saw, Yu; Duc, Nguyen; Haque, Md.; Rahman, Md.; Islam, Md.; Mostofa, Md.
Abstract Background We aimed to examine the influence of witnessing father-to-mother violence on: 1) perpetration of intimate partner violence (IPV); and 2) endorsement of attitudes justifying wife beating in Bangladesh. Methods This paper used data from the 2007 Bangladesh Demographic Health Survey. The analyses were based on the responses of 3374 ever-married men. Exposure to IPV was determined by men's self-reports of witnessing inter-parental violence in childhood. We used adjusted binary logistic regression models to assess the influence of exposure on husbands' perpetration of IPV and their endorsement of attitudes justifying wife beating. Results Nearly 60% of men reported violent behaviour towards an intimate partner and 35.7% endorsed attitudes justifying spousal abuse. Men who witnessed father-to-mother violence had higher odds of reporting any physical or sexual IPV (adjusted OR [AOR] = 3.26; 95% CI = 2.61, 4.06). Men who had witnessed father-to-mother violence were also 1.34 times (95% CI = 1.08, 1.65) more likely endorse attitudes justifying spousal abuse. Conclusions Committing violence against an intimate partner is an all too frequent practice among men in Bangladesh. The study indicated that men who had witnessed father-to-mother violence were more likley to perpetrate IPV, suggesting an intergenerational transmission of violence. This transmission of violence may operate through the learning and modelling of attitudes favourable to spousal abuse. In support of this, witnnessing inter-parental violence was also associated with the endorsement of attitudes justifying spousal abuse. Our findings indicate the continued importance of efforts to identify and assist boys who have witnessed domestic violence and suggest such efforts should aim to change not just behaviours but also attitudes that facilitate such violence.